Adjustment of deferred compensation schemes, fairness concerns, and hiring of older workers - Christian Pfeifer (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
Hutchens (1986, Journal of Labor Economics 4(4), pp. 439-457) argues that deferred compensation schemes impose fixed-costs to firms and, therefore, they employ older workers but prefer to hire younger workers. This paper shows that deferred compensation can be a recruitment barrier even without these fixed-costs, because adjustments of wage-tenure profiles for older new entrants can lead to adverse incentive effects from a fairness perspective. A personnel data set and a linked employeremployee data set reveal that wage-tenure profiles of white-collar workers are indeed adjusted according to entry age but that firms still hire few older workers.
Keywords: J14; J31; J33; M51; M52; 330; Deferred compensation; entry age; fairness; internal labor markets; wages